Mind Over Stress: Membangun Lingkungan Kerja Positif dengan Manajemen Stres yang Efektif - Nabila Mutiara Aida; Nazira Hayya Qanita; Harmon, Harmon (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Workplace stress remains a critical issue undermining employee well-being and organizational performance. This qualitative study explores stress management strategies through the mind over stress lens, utilizing open-ended survey responses from employees to capture nuanced experiences. Key stressors identified include excessive workloads, rigid deadlines, and interpersonal conflicts, with coping mechanisms ranging from sleep to recreational activities. Findings reveal gaps in organizational support, particularly for young employees and those in supervisory roles. The study advocates for mental health programs, flexible work policies, and safer communication channels to transform stress into a manageable challenge. Emphasizing qualitative insights, this research highlights the need for culturally adaptive interventions in workplace stress management.